2013
DOI: 10.1074/jbc.m113.472654
|View full text |Cite
|
Sign up to set email alerts
|

An Out-of-frame Overlapping Reading Frame in the Ataxin-1 Coding Sequence Encodes a Novel Ataxin-1 Interacting Protein

Abstract: Background:The spinocerebellar ataxia type 1 (SCA1) gene encoding ataxin-1 (ATXN1) contains an alternative open reading frame overlapping the ATXN1 coding sequence. Results: The alternative ATXN1 protein is constitutively co-expressed and interacts with ATXN1 N terminus. Alternative ATXN1 is also an RNA binding protein. Conclusion:ATXN1 is a genuine dual coding gene. Significance: Alternative ATXN1 may regulate the function of ATXN1 in physiological and pathological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 48 publications
5
59
0
Order By: Relevance
“…Other than the rat Adora2a gene, only three other dual coding genes containing alternative reading frames have been reported to date (7,8,53). For these three genes, a novel protein product was found to be translated from a transcript that was initially identified for the translation of another protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than the rat Adora2a gene, only three other dual coding genes containing alternative reading frames have been reported to date (7,8,53). For these three genes, a novel protein product was found to be translated from a transcript that was initially identified for the translation of another protein.…”
Section: Discussionmentioning
confidence: 99%
“…interaction between the PrP and AltPrP proteins has been reported. During the preparation of this manuscript, a new dual coding gene (ATXN1) containing alternative reading frames was reported (53). The newly identified Alt-ATXN1 protein is translated from a downstream AUG (ϩ3 frame) of the ATXN1 gene and functions as a novel interacting protein of the ATXN1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, hundreds of unannotated ORFs overlapping a canonical CDS have been described as well (Vanderperre et al 2011(Vanderperre et al , 2013Bergeron et al 2013;Slavoff et al 2013). These ORFs are at the same locus as an annotated CDS but encoded in an alternative reading frame and can either partially overlap the CDS or be completely nested within it.…”
Section: Polycistronic Regions: Overlapping Orfs On One Mrnamentioning
confidence: 99%
“…The now irrefutable existence of "alternative" proteins Recent work has revealed that genomes harbor many nonannotated open reading frames (ORFs) (Vanderperre et al 2011;Bergeron et al 2013;Anderson et al 2015;Mouilleron et al 2016;D'Lima et al 2017;Plaza et al 2017). Although two decades have passed since the first eukaryotic genome was sequenced, assigning translated ORFs to genetic loci remains a daunting task (Basrai et al 1997;Claverie et al 1997;Ladoukakis et al 2011).…”
mentioning
confidence: 99%
“…Understanding the mechanisms of the translation of oORFs in tumor cells is important in the investigation of tumor immunology. Recent studies have characterised two oPEPs encoded from alternative proteins in human cell lines, AltPrP (Vanderperre et al, 2011) and AltATXN1 (Bergeron et al, 2013). Although only a few dPEPs have been identified, they are found to be translated from dORFs via leaky scanning and ribosomal reinitiation mechanisms or translated as a ribosomal entry site contained on the 3′UTR (Mercer et al, 2011).…”
Section: Opeps/ Dpepsmentioning
confidence: 99%